Combining Stakeholder-Engaged Research and the Life Participation Approach to Aphasia: A Pilot Survey on the Aphasia Group Experience. Issue 1 (January 2023) - Szabo, Gretchen; Obermeyer, Jessica; Cauthorn, Angelique; Hornbostel, Michael; Flacco, Joe
Abstract : Stakeholder-engaged research (SER) is common in many health-related fields and is gaining momentum in aphasiology. Stakeholder-engaged research shares many of the same goals and values as the Life Participation Approach to Aphasia (LPAA). The aim of this article is to identify how these two frameworks complement each other and can be applied to aphasia research. This is accomplished by first defining SER and highlighting associated benefits and challenges and then exploring the ways that SER and LPAA's core values support each other. The authors' SER project is discussed to illustrate the synergy between SER and LPAA and highlight the potential research and clinical impacts of expanding the use of SER in aphasiology.